What is Gorgias’ ‘not being’? A brief journey through the Treatise, the Apology of Palamedes and the Encomium of Helen - Erminia Di Iulio (Archai: Revista de Estudos sobre as Origens do Pensamento Ocidental, 2021)
Assuming that a nihilist reading of Gorgias’ thought is to be ruled out, the issue of ‘not being’ remains one of the thorniest in his philosophy; indeed, it is fair to conclude that Gorgias is deeply concerned with ‘not being’. But what, after all, is Gorgias’ ‘not being’? This paper aims to answer this crucial question, by taking into consideration Gorgias’ main texts (i.e. the Treatise, the Apology of Palamedes and the Encomium of Helen). Each of them provides a serious – although not always explicit – account of ‘not being’. Overall, the aim is to show that Gorgias’ account of ‘not being’ is not concerned with ‘non-existence’ at all. It is deeply concerned, however, with falsehood and language. The paper will, therefore, be structured as follows: in part 1, the Treatise and specifically the the first section of the Particular Proof will be addressed and its ‘linguistic’ conception of ‘not-being’ fully exploited; in part 2, the Apology of Palamedes will be taken into account, in order to enucleate its ‘not-being-as-falsehood’ argument; the results from part 1 and part 2 will allow us, in part 3, to provide an analysis of the Encomium of Helen which points at its underlying conception of ‘not-being’.